Surface morphology effects on droplet spreading and rebound dynamics on subcooled superhydrophobic surfaces - Matic Može; Yuheng Shang; Samo Jereb; Nina Kovač; Miha Štucin; Tim Štrus; Peter Rodič; Matevž Zupančič; Maria Rosaria Vetrano; Iztok Golobič (Scientific Reports)
Abstract Subcooled superhydrophobic surfaces have notable applications in aerospace, energy, and refrigeration industries. Superhydrophobic behavior can be achieved with different microscale surface morphologies which can impact the water repellency and icephobicity of the surface. To comprehensively study how surface microstructure influences the spreading, rebounding, and freezing behavior of impacting droplets at various surface temperatures and droplet velocities, several types of surfaces were prepared within this study. Specifically, the effect of structure depth (approx. 3–30 μm) and of the structure type (randomized structure or directional microchannels) was investigated by preparing deep and shallow laser-made structures with either stochastic or deterministic features. Droplet impact tests were performed at Weber numbers between 50 and 185 and across surface temperatures from 25 °C to -30 °C. Surface morphology had a minimal effect on the maximum spreading factor, which was otherwise found to decrease by up to 9.5% when reducing the surface temperature from 25 °C to -30 °C. High-speed imaging revealed that the poorest rebound performance across all surfaces occurred at We ≅ 120, where the transition from the regular rebound to the splashing regime led to a higher prevalence of partial rebounds or full adhesion compared to We ≅ 50 or We ≅ 185. An average contact time of 11.1 ms was recorded across all four superhydrophobic surfaces and was largely independent of the surface microstructure. Under subcooled conditions with possible phase change, surface micro-/nanostructure affects droplet impact dynamics beyond static wetting consideration. Our findings show that microstructure depth and solid-liquid contact fraction significantly influence droplet rebound and/or adhesion on subcooled surfaces. Contact times increased significantly as the surface temperature was decreased and partial adhesion of the droplet was detected if the contact time exceeded ~ 20 ms. Higher relative humidity led to frost formation and hence to greater energy dissipation and droplet pinning during the receding phase, preventing a full rebound, which was independent of the surface morphology. Overall, shallow-featured surfaces exhibited superior water repellency at subcooled temperatures, attributed to their lower solid-liquid contact fraction.